BALANCED VARIABLE ADDITION IN LINEAR MODELS. (13th February 2018) - De Luca, Giuseppe; Magnus, Jan R.; Peracchi, Franco
Abstract: This paper studies what happens when we move from a short regression to a long regression in a setting where both regressions are subject to misspecification. In this setup, the least‐squares estimator in the long regression may have larger inconsistency than the least‐squares estimator in the short regression. We provide a simple interpretation for the comparison of the inconsistencies and study under which conditions the additional regressors in the long regression represent a "balanced addition" to the short regression.